PENGARUH CORPORATE GOVERNANCE, BOOK TAX DIFFERENCES TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE TAHUN 2014-2016) - Yenny Dwi Handayani (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to examine the effect of corporate governance, book tax differences on earnings management. Corporate governance in this study uses a proxy of the effectiveness of the board of commissioners and the effectiveness of the audit committee developed by Hermawan Ancella (2009). Using the consumer goods manufacturing sector listed on the Stock Exchange in the 2014-2016 period as a research sample with 99 observation data. Data analysis techniques using multiple liner regression, with SPSS version 21 software. The results showed that the effectiveness of the board of commissioners has no effect on earnings management, audit committee effectiveness does not affect earnings management, permanent differences have a significant positive effect on earnings management, time/ temporary differences affect on earnings management.